Evaluation of Cenchrus purpureus varieties during its establishment in western Cuba - Ruiz, T. E.; Febles, G.; Vasallo, J.; Díaz, H. (Cuban Journal of Agricultural Science, 2017)
Under dry conditions the establishment of eight varieties of Cenchrus purpureus, obtained by crossing and tissue culture in the Institute of Animal Science, Cuba, was evaluated. A random block design with five replications was applied. The varieties were: 115 (control), 442, 423, 30, H-48, 457, H-31 and 452. The highest number of stems/bunch was observed in materials H-31 (8.1), 452 (8.2), 423 (7.6) and H-48 (7.5) and the highest percentage of dead stems (P = 0.0002) at 423 (22 %) and H-48 (15 %). The varieties with the highest height (P <0.0001) were the 30 (170.0cm), 457 (160.4 cm) and H-48 (156.4cm), and had lower height 442 (89.8cm). The highest number of leaves (P <0.0001) was observed in H-31 (231.7) and 452 (210.1) and the lowest in 30 (102.4). The percentage of green leaf of the total (P <0.0001) was higher for the H-31 (51.3 %) and the lowest for 115 (30.3 %), 423 (29.9 %) and H-48 (31.2 %). The highest number of internodes per stem was found in 115 (16.4), followed by 30 (13.7), and was lower in 442 (6.9) and 452 (8.7) (P <0.0001). The best yield (P = 0.0010) was 442 (7.1t / ha DM), and the worst was 115 (2.1t / ha DM) and 457 (1.7t / ha DM). In 442, 451 and H-31 outstanding values in several of the evaluated indicators were registered. This was not the case for H-48 and 30. It is concluded that the varieties studied showed differences in their growth at the establishment time, although this was not affected. It is recommended to continue the evaluation under cutting or grazing. Key words: evaluation, establishment, grasses